The A1g Mode in the Hg-1201 Phonon Spectrum as an Indicator of N→S Transition - Dovhyj, Ya. (Ukrainian Journal of Physics, 2022)
By analyzing the structure of and the temperature changes in HgBa2CuO4+y phonon spectra, the electron-phonon coupling constant g has been determined for the first time. It is shown that this compound is a superconductor with strong coupling. A frequency interval around 60.4 meV in the HgBa2CuO4+y phonon spectrum, which may be classed as a "soft mode", is revealed. The dominant partial contribution to the density of phonon states in that spectral range is found to be given by O(2) atomic vibrations.